ALEXEY TURBIN ‘S INITIATION PLOT IN THE WHITE GUARD NOVEL BY M.A. BULGAKOV - Guzel M. Ibatullina; Maria M. Krivda (Sovremennye Issledovaniâ Socialʹnyh Problem, 2022)
Background. The problem of the functioning of archetypal plots and related images and motifs in the artistic structure of the novel The White Guard by Mikhail Bulgakov remains practically unexplored in literary criticism. This also applies to the episode of the meeting between Alexei Turbin and Julia Reiss, in which the logic of the initiation plot is revealed, implemented in the text through a system of folklore-fairytale and mythological references that require detailed analysis and interpretation.